Transformation of clay minerals in nanoparticles of several zonal soils in China - Zhang, Zhi Yi; Huang, Li; Liu, Fan; Wang, Ming Kuang; Ndzana, Georges Martial; Liu, Zhi Jie (Journal of soils and sediments, 2019)
Purpose Clay minerals significantly affect the physical, chemical, and biological processes of soils. They undergo spontaneous modification and transformation depending to the climatic conditions. Information concerning the compositions and transformation of clay minerals in nanoparticle colloids (NPs) (25–100 nm) is severely lacking. Studying clay mineral transformation is important approach to understand soil formation. This study was conducted to determine the transformation sequence of clay minerals in several zonal soil NPs. Materials and methods Four soils (Haplustalf, Alf-1; Hapludalf, Alf-2; Hapludults, Ult-1 and Ult-2) were collected from B horizons developed under three different climatic zones of China. Alf-1 (36° 05′ N and 117° 24′ E) was located under a warm temperate zone and Alf-2 (30° 38′ N and 115° 26′ E), Ult-1 (29° 13′ N and 113° 46′ E), and Ult-2 (19° 27′ N and 109° 17′ E) under a subtropical zone. The clay particles (< 2000 nm) (CPs) and nanoparticles (25–100 nm) (NPs) of tested soils were separated. The element composition of CPs and NPs was identified by microwave digestion method. The mineralogy and chemical bonding of clay minerals were studied by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR). Results and discussion With decreasing latitude, NPs and CPs showed that the molar ratio of SiO 2 to Al 2 O 3 trends to diminish, indicating the phenomenon of desilication and allitization in the tested soils. XRD analysis revealed that the main clay mineral of Alf-1 NPs was illite, followed by vermiculite, kaolinite, and kaolinite interstratified minerals (KIMs). The clay minerals of Alf-2, Ult-1, and Ult-2 NPs were dominated by kaolinite (and KIMs), followed by illite, with a little content of hydroxyl-interlayered vermiculite (HIV) in Ult-1 NPs and trace content of gibbsite in Ult-2 NPs. With decreasing latitude, vermiculite and HIV decreased in NPs. When compared to CPs, smectite as well as illite-vermiculite mix-layer mineral (I-V) and illite-HIV mix-layer mineral (I-HIV) were not detected in NPs. The analysis of d060 region by XRD showed that with decreasing latitude, the main clay minerals in NPs were dioctahedral minerals (e.g., illite or kaolinite). These clay minerals resulted from the transformation of trioctahedral minerals in CPs. The disappearance of 2:1 swelling minerals and trioctahedral minerals showed that the NPs were more susceptible to weathering than CPs. Conclusions With decreasing latitude, the transformation of clay minerals followed the sequence of illite → HIV → kaolinite → gibbsite in tested NPs.